The way aesthetic needs affects the relationship between aesthetic responsiveness and creativity - Xiaoxiao Dou; Yannan Zhang; Xiao Wang; Yan Zhang; Ruifeng Hou (PLoS ONE, 2025)
Although the study of beauty and its education is expanding, there is still a scarcity of research surrounding the development of our minds and their responses to these emotions. The goal of this study was to look at how the way we respond to beauty connects with creativity, and how our need for beauty influences this connection. A total of 748 university students participated in the study conducted in China. The participants filled out anonymous surveys on a website. The surveys included three tools: the Aesthetic Needs Scale (ANS), the Aesthetic Responsiveness Assessment (AReA), and the Williams Creative Tendency Scale (WCTS). A positive connection was found between all three factors studied. Aesthetic needs play a role in how the assessment of aesthetic responsiveness relates to creativity. This means that people who score high on the aesthetic responsiveness tend to be more creative, especially if they also have strong aesthetic needs.